Factors related to household food insecurity among the Orang Kintak in Malaysia - Nor Haidanadia Hasni; Sharina Abdul Halim; Sarah Aziz (Penerbit Universiti Kebangsaan Malaysia, 2025)
Malaysia, bestowed with richness in natural forest resources, is habitat to flora and fauna that are crucial in balancing the ecosystem. Forest is not only home but also a provider to indigenous people needs, such as food, materials, medicine, spirituality and recreation. Thus, sustainability and vitality of the forest are crucial to ensure food security amongst indigenous people, like Orang Kintak in Pengkalan Usu, Perak, whom are dependent upon forest resources for their well-being and survival. A total of 42 respondents, selected among the Orang Kintak from the Negrito tribe were sampled using both quantitative and qualitative approaches. Based on the vulnerability factor, main findings of study indicated economic, natural and social factors have affected the food security of Orang Kintak to the point that their livelihoods have now became increasingly threatened. The deterioration in their lives were observed not only due to the destruction of their surrounding environment but also they suffered humanitarian crisis resulting from social and economic changes. Orang Kintak communities go through very difficult times when natural resources continue to decrease and difficult to obtain. Forest encroachment activities have caused indigenous foraging area to shrink, whilst economic and social factors have affected availability and stability of food supply resulting in the threat of poverty, malnutrition, psychological stress and deterioration of the Orang Kintak health in general.